The Development of An Application for Learning How To Use Combined Hormonal Contraceptive Pills - Pansuwan, Kornkarn; Klankhajhon, Sirikanok (Jurnal Keperawatan Soedirman, 2023)
Unintended pregnancy has been a significant global health issue. This study aimed to develop an application for learning how to use combined hormonal contraceptive pills and examine the application’s quality and learning satisfaction. The application was developed in four stages: 1) reviewing the evidence-based practice, 2) designing the structure, 3) developing the application, and 4) checking the application’s accuracy. The quality of the application was tested through questionnaires. A convenience sampling of 40 women aged 20-40 years were selected. The respondents were women who used combined hormonal contraceptive pills and had no previous experience using them in the urban community of Phitsanulok, Thailand, between January and April 2022. Descriptive statistics were used. Consultants and experts checked the research findings and revealed that the application was accurate. The computer and information technology quality of the application for learning based on the Android operating system was high (X̅= 4.00, S.D. = 0.31). The content quality of the application and the satisfaction were also at a high level (X̅= 4.10, S.D. = 0.36; X̅= 4.33, S.D. = 0.52). The findings demonstrated that developing an application for learning how to use combined hormonal contraceptive pills can enhance the effectiveness of contraceptive knowledge and use.